(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
The Pharmaceutical Assistance Cycle (PA) is the basis for healthcare services through which pharmaceutical assistance and expertise can be implemented in a functional and structured way to meet public health demands, adhere to the Brazilian Ministry of Health vision, and strike a balance in the contemporary struggle for health equity. The aim of this research is to analyze the effectiveness of the PA cycle in the city of Romelândia (SC), through a study conducted at a Primary Healthcare Unit in the municipality. For the study, 120 patients (service users) and seven healthcare professionals were interviewed. The majority of patients confirmed that they were given advice and instruction on dosage during the dispensing process, as well as advice on the recommended use of medicines and course duration. A small number of service users, 4.1%, said that they received instructions on adverse drug interactions; 36.6% commented on a lack of access to medicines available in the municipal pharmacy, and 71.4% of the health professionals interviewed, identified non-availability of medicines in the pharmacy as the most pressing and telling problem facing the service. There is also no local Pharmacy and Therapeutics Committee, and the only selection criteria is the Ministry of Health essential medicines list. Our study has therefore identified several weaknesses facing the city healthcare service, namely: the shortage of medicines; a lack of resolute professional communication between pharmacist and service user; a lack of patient counseling during the dispensing process, and a lack of communication regarding patient follow-up treatment and wellbeing.